2016
DOI: 10.1002/jbm.a.35934
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐biofilm properties of bioactive glasses embedding organic active compounds

Abstract: Bioactive glasses (BGs) are promising materials for bone repair due to their desirable properties such as osteoconductivity, biodegradability, angiogenic potential, and antibacterial activity. Ionic dissolution products from bioactive glasses increase the medium pH inhibiting surrounding bacteria proliferation. The activity of BGs against biofilm formation has been enhanced by incorporating organic antibacterial compounds. The aim of this review was to summarize evidence in literature which assesses the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 64 publications
(159 reference statements)
0
32
0
1
Order By: Relevance
“…The antibacterial effect revealed by BG has been attributed to the ion release capability in increasing the pH of the surrounding medium that can affect planktonic bacteria growth . Most of the studies report that the BG antibacterial effect against specific planktonic bacteria do not reflect realistic conditions of biofilm growth and pathogenicity at infected areas . Biofilm is a well‐organized microbial community embedded in an extracellular polymeric matrix composed of polysaccharides, nucleic acids, proteins and water, that adheres to different surfaces such as teeth, rehabilitation synthetic materials, bone, and soft tissues .…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial effect revealed by BG has been attributed to the ion release capability in increasing the pH of the surrounding medium that can affect planktonic bacteria growth . Most of the studies report that the BG antibacterial effect against specific planktonic bacteria do not reflect realistic conditions of biofilm growth and pathogenicity at infected areas . Biofilm is a well‐organized microbial community embedded in an extracellular polymeric matrix composed of polysaccharides, nucleic acids, proteins and water, that adheres to different surfaces such as teeth, rehabilitation synthetic materials, bone, and soft tissues .…”
Section: Introductionmentioning
confidence: 99%
“…So even though,10.7% of the treated cases showed BOP in the follow-up evaluation, this positive parameter was not considered as presence of disease since it was not correlated with other inflammation and bone loss signs in the treated implants.Furthermore, various studies have claimed that one of the main etiological factors of PI is plaque accumulation 4,5,31,32. It has been reported that implantoplasty 20,33 will provide a less favorable surface for biofilm adhesion, since biofilm is attracted and also protected in rough surfaces 34,35. It has been reported that implantoplasty 20,33 will provide a less favorable surface for biofilm adhesion, since biofilm is attracted and also protected in rough surfaces 34,35.…”
mentioning
confidence: 99%
“…BGs have been modified over the years with the incorporation of diverse antibacterial and antibiofilm agents to counteract bone infection. Various studies have reported the incorporation of metal oxides, antibiotics and other organic agents into BGs; however, there is no consensus until present day concerning which antibiofilm agent is the most effective for bone infection treatment . Indeed BG of “S53P4” composition is commercially available as an effective agent to counteract osteomyelitis conditions .…”
Section: Discussionmentioning
confidence: 99%
“…developed the first bioactive glass (BG) of composition: 46.1 mol %, SiO 2 24.4 mol % Na 2 O, 26.9 mol % CaO, and 2.6 mol % P 2 O 5 (known as the 45S5 BG composition), with the purpose of generating a biomaterial that could bond to bone for orthopedic applications . After many years of intensive research in the field, BGs have been demonstrated to be outstanding biomaterials due to their desirable characteristics such as high bioactivity, osteogenic stimulation, angiogenic effect, ability to bond to soft tissues, high biocompatibility, and antibacterial activity induced by their ion release capability . It is well established that highly bioactive synthetic glasses bond to bone through the formation of a hydroxyl‐carbonate apatite (HCAp) layer, which mimics the mineral phase of bone; thus, resulting in a biological match between BGs and bone tissue .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation